Oral health knowledge, attitudes and behaviours of 11-12 year old orang asli children in Cameron Highland, Pahang / Rianti Samosir Syam - Rianti , Samosir Syam (2017)
The objectives of this study were to assess the levels of oral health knowledge, attitudes and related behaviours of 11 – 12 year old Orang Asli (OA) schoolchildren in Cameron Highland, Pahang, and to develop a suitable oral health education (OHE) module for OA primary school children. Methods: This was a cross-sectional study using a self-filled questionnaire. The study population was OA primary schoolchildren in the Pahang state. The sample population was all OA primary schoolchildren in Cameron Highland (CH) district, Pahang. The inclusion criteria were 11-12 year old OA children (Year 5-6) who attended OA primary schools, whose parents were from OA descendents, and who were able to read and write. The questionnaire was adopted from a questionnaire used in a local study. It was validated for use by the OA children to assess OA children’s oral health knowledge (OHK), attitudes (OHA), and related behaviours (OHB). Ethical approval was granted by the Medical Ethics Committee, Faculty of Dentistry (Ethic No: DF DP 1206/0078 (L)). Permissions to conduct the study were obtained from the Jabatan Kemajuan Orang Asli (JAKOA), Ministry of Education, State and District Education Departments, school headmasters and parents. Result: The response rate was 91.2%. The majority of OA children had poor scores on 7 of 9 OHK items (score range = 55.1-76.7%), representing 77.8% of OHK items. About one-third (33.5%) had moderate score on item ‘Brushing with fluoride toothpaste can prevent tooth decay’, and less than half (40.5%) had moderate score on item ‘We are encouraged to brush our teeth twice a day’. In terms of oral health attitudes, the majority of OA children had poor scores on six of 13 OHA items (score range = 64.8-79.7%), representing 46.2% of OHA items. The poor scores were related to OHA items ‘sweet foods and drinks is good for the teeth’ (65.6%), ‘sweet foods and beverage should be sold in school canteen’ (64.8%), ‘chewing betel nuts will makes teeth look beautiful’ (75.8%), and ‘chewing betel nut will be add freshness to mouth’ (79.7%). However, the majority had good to moderate scores in all five items iv related to toothbrushing. In terms of oral health behaviours, the majority of OA children brushed their teeth >2 times/day (83.7%), and used fluoride toothpaste >2 times/day (80.2%). However, a large majority (83.3%) had experienced chewing betel nut with 67.4% chewed >1 time/day. The majority of OA children consumed sugary/carbonated drinks >2 times/day (53.8%), consumed sugary foods >2 times/day (56.3%) and rinsed their mouth after meal >2 times/day (54.6%). A small proportion smoked cigarettes (4.0%). An OHE package was developed based on the study findings. Conclusion: This study showed that OA schoolchildren in Cameron Highland had poor oral health knowledge, attitudes and behaviours. Subsequently, suitable OHE package was developed for use in OA primary schools to improve OA children’s oral health knowledge, attitude, behaviors, and oral health status.